Global dispersal and adaptive evolution of domestic cattle: A genomic perspective - Xiaoting Xia; Kaixing Qu; Yan Wang; Sinding, M.H.S.; Fuwen Wang; Quratulain Hanif; Ahmed, Z.; Lenstra, J.A.; Han Jianlin; Chuzhao Lei; Ningbo Chen (Springer, 2023)
Domestic cattle have spread across the globe and inhabit variable and unpredictable environments. They have been exposed to a plethora of selective pressures and have adapted to a variety of local ecological and management conditions, including UV exposure, diseases, and stall-feeding systems. These selective pressures have resulted in unique and important phenotypic and genetic differences among modern cattle breeds/populations. Ongoing efforts to sequence the genomes of local and commercial cattle breeds/populations, along with the growing availability of ancient bovid DNA data, have significantly advanced our understanding of the genomic architecture, recent evolution of complex traits, common diseases, and local adaptation in cattle. Here, we review the origin and spread of domestic cattle and illustrate the environmental adaptations of local cattle breeds/populations.